Ranibizumab 0.5 mg treat-and-extend regimen for diabetic macular oedema: the RETAIN study - Prünte, Christian; Fajnkuchen, Franck; Mahmood, Sajjad; Ricci, Federico; Hatz, Katja; Studnička, Jan; Bezlyak, Vladimir; Parikh, Soumil; Stubbings, William John; Wenzel, Andreas; Figueira, João; RETAIN Study Group (The British journal of ophthalmology, 2016)
AIMS: To demonstrate non-inferiority of ranibizumab treat-and-extend (T&E) with/without laser to ranibizumab pro re nata (PRN) for best-corrected visual acuity (BCVA) in patients with diabetic macular oedema (DMO). METHODS: A 24-month single-masked study with patients randomised 1:1:1 to T&E+laser (n=121), T&E (n=128) or PRN (control; n=123). All patients received monthly injections until BCVA stabilisation. The investigator decided on re-treatment in the PRN and treatment-interval adaptations in the T&E groups based on loss of BCVA stability due to DMO activity. Likewise, laser treatment was at investigator's discretion. Collectively, these features reflect a real-life scenario. Endpoints included mean average change in BCVA from baseline to months 1-12 (primary), mean BCVA change from baseline to months 12 and 24, treatment exposure and safety profile. RESULTS: Both T&E regimens were non-inferior to PRN based on mean average BCVA change from baseline to months 1-12 (T&E+laser: +5.9 and T&E: +6.1 vs PRN: +6.2 letters; both p<0.0001). Mean BCVA change at month 24 was similar across groups (+8.3, +6.5 and +8.1 letters, respectively). The mean number of injections was 12.4 and 12.8 in the T&E+laser and T&E groups and 10.7 in the PRN group. The T&E regimens showed 46% reduction in the number of clinic visits. Over 70% of patients maintained their BCVA, with treatment intervals of ≥2 months over 24 months. Safety profile was consistent with that described in the product information. CONCLUSIONS: T&E is a feasible treatment option for patients with DMO, with a potential to reduce treatment burden. Slightly more injections were required versus PRN, likely due to the specifics of the T&E regimen applied here. TRIAL REGISTRATION NUMBER: NCT01171976.
Keywords: Angiogenesis Inhibitors; Dose-Response Relationship, Drug; Macula Lutea; vztah mezi dávkou a účinkem léčiva; Macular Edema; injekce intravitreální; vaskulární endoteliální růstový faktor A; Intravitreal Injections; Retrospective Studies; Time Factors; výsledek terapie; Single-Blind Method; Middle Aged; mužské pohlaví; jednoduchá slepá metoda; Ranibizumab; makulární edém; Diabetic Retinopathy; Treatment Medical; Vision; Follow-Up Studies; následné studie; macula lutea; Macula; ženské pohlaví; optická koherentní tomografie; retrospektivní studie; Humans; zraková ostrost; Tomography, Optical Coherence; Visual Acuity; časové faktory; lidé středního věku; ranibizumab; Vascular Endothelial Growth Factor A; Clinical Trial; inhibitory angiogeneze; Female; diabetická retinopatie; Treatment Outcome; lidé; Male; Treatment Lasers